Right heart chambers geometry and function in patients with the atrial and the ventricular phenotypes of functional tricuspid regurgitation. (4th February 2022) - Florescu, D; Muraru, D; Florescu, C; Gavazzoni, M; Volpato, V; Caravita, S; Tomaselli, M; Balseanu, TA; Parati, G; Badano, LP
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction — Atrial functional tricuspid regurgitation (A-FTR) is a recently defined phenotype of FTR associated with persistent/permanent atrial fibrillation. Differently from the classical ventricular form of FTR (V-FTR), patients with A-FTR might present with severely dilated right atrium (RA) and tricuspid annulus (TA), and with preserved right ventricular (RV) size and systolic function. However, the geometry and function of the RV, RA and TA in patients with A-FTR and V-FTR remain to be systematically evaluated. Purpose — Accordingly, we sought to: i. study the geometry and function of the RV, RA and TA in A-FTR by two- and three-dimensional transthoracic echocardiography; and ii. compare them with those found in V-FTR. Methods — We prospectively analysed 113 (44 men, age 68 ± 18 years) FTR patients (A-FTR = 55 and V-FTR = 58) that were compared to two groups of age- and sex-matched controls to develop the respective Z-scores. Results — The severity of FTR, and the degree of TA dilation were similar in A-FTR and V-FTR patients. The Z-scores of RV size were significantly larger, and those of RV function were significantly lower in V-FTR than in A-FTR (p < 0.001 for all). The RA was significantly enlarged in both A-FTR and V-FTR compared to controls (p < 0.001, Z-scores > 2), with similar RA maximal volumes (RAVmax) between A-FTR and V-FTR (p = 0.2). Whereas, the RA minimal volumes (RAVmin) were significantly larger in A-FTR than in V-FTR (p = 0.001). Conclusion — Despite similar degrees of FTR, RAVmax and TA size, A-FTR patients show larger RAVmin than V-FTR patients. Conversely, V-FTR patients show dilated, more elliptic and dysfunctional RV than A-FTR patients.